Uso de plantas medicinais por discentes do Bacharelado Interdisciplinar em Ciência e Tecnologia-Unipampa - Santos, Catiane da Silva dos (2019)
In Brazil, the understanding of the properties of medicinal plants is a of the greatest riches of indigenous culture, a traditional wisdom passed down from generation to generation. The work was developed at the UNIPAMPA (Federal University of the Pampa) campus Itaqui, between April and May 2019. A Questionnaire was developed with questions regarding the socioeconomic and cultural profile of the interviewees and their use in relation to plant consumption 50 students were interviewed, the questionnaire was applied in the classroom. According to the traditional knowledge the plants were referenced only by the popular name and through the aid of specialized bibliographic reference were confirmed and identified by the scientific name. The use of medicinal plants is millenarian and is part of the culture of different peoples, as observed in the questionnaires filled out by the students. As for the profile of the interviewees, it was observed that students who use medicinal plants 56% were 19 to 25 years and 25% between 26 and 35 years. It is interesting to notice the use of medicinal plants in the different age groups addressed in the interview. ie the use of medicinal plants is not restricted to a single age group, younger people in the age group between 18 and 25 years also consume or have knowledge about these medicinal plants. It was verified that 72% use medicinal plants for the treatment of their diseases, which usually make use of them by influence of the family members. About 61% of the interviewees use medicinal plants from their own vegetable garden, 25% of them from street vendors. The medicinal plants most cited in the work were: Achyrocline satureoides and Peumus boldus/ Plectranthus barbatus, and the reported use in the research is in accordance with the indications in the literature. It is concluded that the extension and improvement of the use and knowledge of traditional medicinal plants, carried out in an appropriate way, contribute significantly to the improvement of the well-being of the interviewees in general.